2013
DOI: 10.1111/brv.12037
|View full text |Cite
|
Sign up to set email alerts
|

Chaperonin 60: a paradoxical, evolutionarily conserved protein family with multiple moonlighting functions

Abstract: Chaperonin 60 is the prototypic molecular chaperone, an essential protein in eukaryotes and prokaryotes, whose sequence conservation provides an excellent basis for phylogenetic analysis. Escherichia coli chaperonin 60 (GroEL), the prototype of this family of proteins, has an established oligomeric-structure-based folding mechanism and a defined population of folding partners. However, there is a growing number of examples of chaperonin 60 proteins whose crystal structures and oligomeric composition are at var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(86 citation statements)
references
References 305 publications
(369 reference statements)
3
83
0
Order By: Relevance
“…As per the convention, groEL gene that is in operonic arrangement with groES has been termed groEL1, while that that exists separately on the genome has been termed groEL2 (Kong et al 1993;Cole et al 1998). Despite high sequence similarity to other chaperonins, functional studies on GroEL2 initially identified it as the immunodominant antigen in the mycobacterial culture filtrates, leading to the search for its immunological roles (Lamb et al 1989;Cehovin et al 2010;Henderson et al 2010Henderson et al , 2013. Therefore, studies that followed focused on understanding the immunological tasks of the Mtb GroELs, which eventually demonstrated that all the chaperonins, GroEL1 (Lewthwaite et al 2001), GroEL2 (Hickey et al 2010), and GroES (Sonnenberg and Belisle 1997), are secreted, with GroEL1 being the more immunopotent (Lewthwaite et al 2001).…”
Section: Multiple Groels In Mycobacteriamentioning
confidence: 99%
“…As per the convention, groEL gene that is in operonic arrangement with groES has been termed groEL1, while that that exists separately on the genome has been termed groEL2 (Kong et al 1993;Cole et al 1998). Despite high sequence similarity to other chaperonins, functional studies on GroEL2 initially identified it as the immunodominant antigen in the mycobacterial culture filtrates, leading to the search for its immunological roles (Lamb et al 1989;Cehovin et al 2010;Henderson et al 2010Henderson et al , 2013. Therefore, studies that followed focused on understanding the immunological tasks of the Mtb GroELs, which eventually demonstrated that all the chaperonins, GroEL1 (Lewthwaite et al 2001), GroEL2 (Hickey et al 2010), and GroES (Sonnenberg and Belisle 1997), are secreted, with GroEL1 being the more immunopotent (Lewthwaite et al 2001).…”
Section: Multiple Groels In Mycobacteriamentioning
confidence: 99%
“…Meanwhile, based on essentially the same basic mechanism involving hydrophobic interaction, the bacterial GroEL-GroES is evolutionarily conserved to regulate many aspects of protein bioprocess in vivo, such as the well-recognized role of driving protein folding, maintaining proteostasis, and membrane protein solubilization, translocation and targeting (Castanie-Cornet et al, 2014;Henderson et al, 2013;Lin et al, 2006). Here, the ability of this remarkable molecular machine to modulate functional cell-free expression of CXCR4 has been examined.…”
Section: Discussionmentioning
confidence: 99%
“…(iii) Some subunits are defined by unique functions, unrelated to protein folding, which would preclude the ability to substitute for each other. Such 'moonlighting' roles have been observed for bacterial as well as mammalian chaperonins and have been discussed extensively in a recent review [31].…”
Section: Multiplicity Of Chloroplast Chaperoninsmentioning
confidence: 91%
“…Heat-shock (p rotecƟon of Rubi sco acƟvase) [44] NdhH folding, assembly of the NDH complex [38] RegulaƟon via calmodulin bindin g [50] Chlo ropl ast di vision (FtsZ ring formaƟon) [40] TRENDS in Plant Science of chaperonin genes in various bacterial species [31,75]. (i) All of the proteins have a similar role, in which case the genes should all be interchangeable, but are differentially expressed, enabling regulation under different conditions.…”
Section: Multiplicity Of Chloroplast Chaperoninsmentioning
confidence: 99%
See 1 more Smart Citation